1996
DOI: 10.1182/blood.v88.11.4359.4359
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of transferrin receptor-positive sickle reticulocytes during continuous or cyclic deoxygenation: role of KCl cotransport and extracellular calcium

Abstract: The K+ efflux that mediates sickle-cell dehydration may occur through several pathways, including two with a high capacity for mediating rapid K+ loss, KCl cotransport and the Ca(2+)-dependent K+ channel [K(Ca2+)]. The rate and pathway of red blood cell (RBC) dehydration most likely depends on cell age and hemoglobin (Hb) composition, with the presence of HbF playing an important role. Oxygenated sickle RBCs have relatively stable cell volume during incubation in vitro, whereas deoxygenated cells become dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…We confirm that Cl Ϫ -independent K ϩ influxes were stimulated as PO 2 was reduced, as expected for mediation via P sickle . In control HbS cells, O 2 -dependence was similar to that in a previous report that involved a different method (passive K ϩ and Na ϩ fluxes) to monitor P sickle (22). Upon addition of 12C79, the stimulation of Cl Ϫ -independent K ϩ influxes occurred at lower PO 2 s, so that in both control cells and those treated with 12C79, the PO 2 s required for half-maximal activation of Cl Ϫ -independent K ϩ influx were similar to those required for half-maximal saturation of HbS with O 2 and half-maximal sickling ( Table 1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We confirm that Cl Ϫ -independent K ϩ influxes were stimulated as PO 2 was reduced, as expected for mediation via P sickle . In control HbS cells, O 2 -dependence was similar to that in a previous report that involved a different method (passive K ϩ and Na ϩ fluxes) to monitor P sickle (22). Upon addition of 12C79, the stimulation of Cl Ϫ -independent K ϩ influxes occurred at lower PO 2 s, so that in both control cells and those treated with 12C79, the PO 2 s required for half-maximal activation of Cl Ϫ -independent K ϩ influx were similar to those required for half-maximal saturation of HbS with O 2 and half-maximal sickling ( Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…While this may appear to suggest a lack of deoxygenation-induced Ca 2ϩ permeability incompatible with the properties of P sickle , it is not a unique finding. Joiner and colleagues (22,62) have shown that measurable transport via the Gardos channel is not always observed in unfractionated HbS cells upon deoxygenation. They suggest that most activity resides in a small subpopulation of HbS cells (perhaps those with least Ca 2ϩ pump activity) or that experimental conditions (for example, duration of deoxygenation, which in some cases may be several hours) are critical to allow sufficient Ca 2ϩ entry via P sickle .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, diluting the cytosol by preswelling of erythrocytes enhances the Ca 2+ sensitivity of breakdown of membrane phospholipid asymmetry as induced by hypotonic haemolysis (Williamson et al, 1985). Along those lines, activation of Ca 2+ -sensitive K + channels participates in the cell shrinkage and deformation of deoxygenized sickle cells (Bookchin et al, 1987;Lew and Bookchin, 1991;Brugnara et al, 1993;Joiner, 1993;Franco et al, 1996), which have most recently been shown to be highly sensitive to apoptosis (Lang et al, 2002b).…”
Section: Resultsmentioning
confidence: 99%
“…K + ‐Cl − cotransport activity can therefore contribute to the development of sickle cells, whose raised microviscosity and reduced deformability (Ellory et al 1989 b ) contribute to vascular occlusion (at least in animal models) and hence to sickle cell disease. The relative importance of K + ‐Cl − cotransport in these processes, compared with that of the Ca 2+ ‐activated K + channel activity (Gardos channel: Gardos, 1958), also abnormally high in sickle cells, has been the subject of considerable research (for example: Ohnishi et al 1986; Ellory et al 1989 b ; Bookchin et al 1991; Apovo et al 1994; Franco et al 1996).…”
mentioning
confidence: 99%